Effect of docetaxel administration on fluid dynamics in mice - Ayana Mawaki; Masushi Kohta; Aya Yoshimura; Toshio Nakatani; Shizuko Nagao; Junko Sugama (Fujita Medical Journal)
Objectives: The taxane chemotherapeutic agent docetaxel has been used as a therapy for various cancers. Some patients receiving docetaxel develop serious problems with fluid retention, which leads to peripheral edema formation, reducing the patient’s quality of life. This study investigated the effect of docetaxel administration on fluid dynamics in mice as a step toward developing advanced preventive measures in nursing. Methods: Mice were administered 10 mg/kg/day of docetaxel intravenously for 5 days as the intervention group or with normal saline as the control group. To investigate fluid dynamics on day 5, the leakage of blood plasma, interstitial fluid volume, and fluid transportation capacity into lymph vessels were evaluated and compared between the two groups. Results: The Miles assay with Evans Blue, an albumin-binding dye, revealed that leakage of blood plasma was significantly increased in the control group compared with the intervention group (p<0.01). Results of the interstitial fluid volume and fluid transportation capacity were similar between the two groups, but the fluid transportation capacity tended to be higher in the intervention group. Conclusions: Docetaxel administration in our mouse model caused the leakage of blood plasma without proteins from the blood vessels into the interstitial tissues, which appeared at the initial stage of edema formation. This model might be useful for assessing the leakage of blood plasma and, subsequently, the development of preventive measures against edema formation.